Arius: Twice a Heretic? Arius and the Human Soul of Jesus Christ - Haugaard, William P. (Church history, 1960)
“Christology was an important element of the earliest Arianism.” So states Raven in the introductory chapters to his study of apollinarianism. This paper will consider the christology of the “earliest′ Arians,” in particular that of Arius himself. Christology has been defined as “the study of the Person of Christ, and in particular of the union in Him of the Divine and human natures.” In the latter “particular” sense, we shall conclude that Arius really had no developed christology. This is not to say, however, that Arius was not christologically concerned in the larger sense of the word; i.e., “the study of the Person of Christ.” It is true to say after Dorner that:We should be very greatly mistaken … if we were to suppose that the Christological labours had meanwhile been totally suspended: on the contrary, in the case of the thinkers of the Church, Christology was the perennial motive of their trinitarian efforts.